Fibroblast-secreted trophic factors contribute with ECM remodeling stimulus and upmodulate osteocyte gene markers in osteoblasts - Costa Fernandes, Célio Jr da [UNESP]; Zambuzzi, Willian Fernando [UNESP] (Elsevier, 2020)
As osteogenesis is a multifactorial mechanism, we wonder whether osteoblast-induced extracellular matrix (ECM) remodeling might be modulated by trophic factors released by fibroblasts in a paracrine signaling manner. To address this issue, fibroblasts were cultured for 72 h under conventional conditions when their conditioned medium was harvested and used to challenge pre-osteoblasts (MC3T3-E1 cells) for 14 days. Preliminarily, we validated the potential effect of fibroblasts in contributing to osteocyte phenotype, which specifically requires significant expression of Dentin Matrix Protein 1 (DMP1; about 10-fold changes) and Sclerostin (SOST; about 7-fold changes), both biomarkers of osteocyte. Fibroblasts also seem contributing to ECM remodeling in osteoblasts, because we detected a high level of both mRNA and enzyme activities of matrix metalloproteinase −9 (MMP-9) as well as a high level of reversion inducing cysteine rich protein with kazal motifs (RECK) transcripts (about 13-fold changes), a membrane-anchored MMP inhibitor, which seems to be a constitutive pathway in osteoblasts. Considering inflammatory panorama and using RTqPCR technology, both IL-13 (about 13-fold changes) and IL-33 (about 5-fold changes) genes were up-expressed in response to the fibroblast-secreted trophic factors, as were the receptor activator of NF-κB ligand (RANKL; about 8-fold changes) and osteoprotegerin (OPG; about 3-fold changes). Although preliminary, these data suggest a stimulus to finely control osteoclastogenesis, and this mechanism reinforces the role of fibroblasts in bone remodeling and homeostasis. Moreover, these results suggest an important crosstalk between fibroblast and osteoblast, when fibroblast-secreted trophic factors upmodulate osteocyte gene markers and contribute to ECM remodeling stimulus in osteoblast.
Keywords: Bone; Crosstalk; Extracellular matrix; Fibroblast; Osteoblast; Osteocyte